Diseases transmitted by ticks - İşler, Hacer; Özdemir, Metin (Infectious diseases and microbiology, 2022)
"The incidence of tick-borne diseases affecting humans has increased with increased travel and exposure to exotic environments. Ticks are important as vectors of European tick-borne encephalitis, Russian summer-spring encephalitis, and Lyme disease in America, Europe, and Asia. No struggle methods used to date have provided complete eradication of ticks and reduced the risk of tick-borne disease transmission. Ticks are still the most important vectors in the transmission of many infectious diseases. The primarily transmitted diseases to humans from ticks can be listed as Crimean Congo Hemorrhagic Fever (CCHF), Lyme disease, Q fever, Tick-borne encephalitis, Mediterranean spotted fever, Monocytic ehrlichiosis, Granulocytic ehrlichiosis, Babesiosis. Besides causing severe health problems in humans, ticks also create significant economic losses on livestock. This group of diseases is more common than thought and can become chronic or show a severe course and result in death without being diagnosed. Tick-borne diseases are incredibly diverse, both biologically and clinically, and symptoms are often non-specific, making recognition and appropriate treatment difficult. We aimed to examine the various disease syndromes in detail from a clinical perspective and support the medical literature for these diseases, which generally occur outside the clinicians' practice field. In the book chapters, the expected risks of the patients, the epidemiology and pathogenesis of the disease, and necessary clinical applications in treatment and follow-up processes will be discussed. We aimed to draw attention to the issues about tick-borne diseases in the light of recent developments and cases. As a ready-made resource, this book will cover basic and recent literature information, which will be very useful for students and professionals in human and veterinary medicine, public health, medical entomology, acarology, and ecology"--Publisher's description.